If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (16y + 1) + -1(5y + -7) = 4y + -5 Reorder the terms: (1 + 16y) + -1(5y + -7) = 4y + -5 Remove parenthesis around (1 + 16y) 1 + 16y + -1(5y + -7) = 4y + -5 Reorder the terms: 1 + 16y + -1(-7 + 5y) = 4y + -5 1 + 16y + (-7 * -1 + 5y * -1) = 4y + -5 1 + 16y + (7 + -5y) = 4y + -5 Reorder the terms: 1 + 7 + 16y + -5y = 4y + -5 Combine like terms: 1 + 7 = 8 8 + 16y + -5y = 4y + -5 Combine like terms: 16y + -5y = 11y 8 + 11y = 4y + -5 Reorder the terms: 8 + 11y = -5 + 4y Solving 8 + 11y = -5 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 8 + 11y + -4y = -5 + 4y + -4y Combine like terms: 11y + -4y = 7y 8 + 7y = -5 + 4y + -4y Combine like terms: 4y + -4y = 0 8 + 7y = -5 + 0 8 + 7y = -5 Add '-8' to each side of the equation. 8 + -8 + 7y = -5 + -8 Combine like terms: 8 + -8 = 0 0 + 7y = -5 + -8 7y = -5 + -8 Combine like terms: -5 + -8 = -13 7y = -13 Divide each side by '7'. y = -1.857142857 Simplifying y = -1.857142857
| 13x+29y=-3 | | 25n=450 | | 4(3q-4)= | | log(x^2+6x+960)=3 | | -8n+1=-6-5 | | T=0.2s+10 | | 4y+8x=120 | | 104=x+(x+5)+5x-6 | | d-(12)=-73 | | 3*x-11=x+33 | | d-(12)=-733 | | 3x+45+7x+5=90 | | h-4=kforj | | -5(3x+2)-x=22 | | -3(x+9)=30 | | 3*x-11=x+34 | | 48x^2-50x+7=0 | | 9x^2-4x+1=0 | | 6x^3-9x^2-2x+3=0 | | 8-9(-4x+7)= | | 46-5=-6y | | 3x+45+7x+5=180 | | 9x+4=8x+6 | | .99=10+.89d | | (18-3x)-(4+2x)=10 | | -4-2(3-x)=-2(x+3) | | -16=6+4+3x | | -6x^3+9x^2-3=0 | | 3=y-n+h | | -8=13-7x | | xy=1+3x | | N=y-n+h |